Depression in adolescents with beta-thalassemia major in Erbil city-Iraq - Liqaa Habeeb Yousif; Selwa Elias Yacoub (Advanced Medical Journal)
Background and objectives: Depression in adolescent is commonly prevalent with higher rates among patients with thalassemia. The aim of this study is to identify the prevalence of depression in adolescent with beta thalassemia ma- jor attending thalassemia main center in Erbil city /Iraq.